(untitled) (Bangladesh Journal of Medical Education, 2026)
Background: Social justice is grounded in the principle that everyone should have equal economic, political, and social rights and opportunities. Objectives: To explore stakeholders’ perspectives on the integration and practice of social justice in the MBBS admission process in Bangladesh. Methods: The study was conducted on teachers and MBBS students in 8 medical colleges in Bangladesh. From all four phases, a total of 200 teachers and 600 students were respondents of this study. A self-administered structured questionnaire was used for data collection. A convenient sampling technique was used for the selection of teachers and students. Results: The study revealed moderate student agreement that MBBS admissions were fair, particularly regarding gender (4.19 ± 0.81) and ethnicity (3.70 ± 1.23), although economic status (3.03 ± 1.45) remained a concern. Teachers showed agreement with similar patterns, noting lower fairness regarding health status (3.0 ± 1.18) and student identity (3.60 ± 1.10). Conclusion: The findings indicate that while stakeholders recognize some aspects of fairness in medical education, significant gaps persist in the integration and practice of social justice. These insights call for comprehensive reforms in curriculum design, institutional policies, and stakeholder engagement to ensure a more equitable and socially just undergraduate medical education system in Bangladesh. BJME: Vol.-17, Issue-01, January, 2026:44-49